Residual polymer stabiliser causes anisotropic electrical conductivity during inkjet printing of metal nanoparticles - Gustavo F. Trindade (Nature Portfolio, 2021)
Inkjet printed metal nanoparticles are known to have lower electrical conductivity than those produced by traditional approaches. Here, anisotropic electrical conductivity is attributed to organic residuals from the metal nanoparticle ink, reducing conductivity.